2002
DOI: 10.1007/s00442-002-0886-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential invasion of a wetland grass explained by tests of nutrients and light availability on establishment and clonal growth.

Abstract: Phalaris arundinacea (Poaceae) is aggressively invading wetlands across North America. We tested the hypotheses that open canopies and increased nutrients facilitate vegetative establishment in the field, using a phytometer (6 rhizome fragments/plot, 24 plots/wetland). In each of three wetlands, phytometers received three levels of an NPK fertilizer or served as controls. Emergence and survival differed among sites (P=0.0005), but not due to NPK addition. P. arundinacea survival was highest in a wet prairie wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
135
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(140 citation statements)
references
References 37 publications
4
135
1
Order By: Relevance
“…However, plants may focus on growing leaves for photosynthesis at the cost of limiting root growth. In the present study, root/leaf mass ratio decreased with increasing water depth overall, indicating that the biomass allocation favors leaf growth rather than root growth, which is thought to be an efficient strategy for plants to adapt to poor light conditions in deep water (Chambers & Kalff 1985;Strand & Weisner 2001;Maurer & Zedler 2002). Meanwhile, photosynthesis of submerged plants is constrained in deep water and there is not enough photosynthate for roots, which, in turn, limits root growth.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, plants may focus on growing leaves for photosynthesis at the cost of limiting root growth. In the present study, root/leaf mass ratio decreased with increasing water depth overall, indicating that the biomass allocation favors leaf growth rather than root growth, which is thought to be an efficient strategy for plants to adapt to poor light conditions in deep water (Chambers & Kalff 1985;Strand & Weisner 2001;Maurer & Zedler 2002). Meanwhile, photosynthesis of submerged plants is constrained in deep water and there is not enough photosynthate for roots, which, in turn, limits root growth.…”
Section: Discussionmentioning
confidence: 53%
“…However, it does not work alone. Water depth works in conjunction with sediment type and other environmental factors such as light, air temperature, wave and flow velocity among others (Sand-Jensen & Søndergaard 1979;Barko et al 1986;Maurer & Zedler 2002). Research indicates that, for many submerged plants, the achievement of maximum summer biomass is impacted by both water depth and sediment composition (Chambers & Kalff 1987).…”
mentioning
confidence: 99%
“…For example, Pysˇek et al (2003) found that novel hybrid invasive genotypes may be produced by rare sexual reproduction, fixed by clonal growth, and presents a previously unknown threat to native vegetation. Maurer and Zedler (2002) suggested that both the resource subsidy from parent clones and resource foraging plasticity contribute to invader's ability to spread rapidly into native vegetation. Reichard and Hamilton (1997) studied the invasive plants of America and also found that clonality may enhance invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Clonality, an important trait enhancing plants' exploitation of ubiquitous environmental heterogeneity, may aid plants to invade new habitats (Maurer and Zedler 2002). Also, clonality can contribute to spatial occupation at a local scale and risk spreading of the clonal plants (Dong 1996b).…”
Section: Introductionmentioning
confidence: 99%
“…Seed germination and early life stages are typically suppressed by higher water salinities and by daily inundation, and only those able to tolerate these harsh physical conditions can become established as seedlings. The clonal life-history strategy for reinvasion of gaps has been important in other systems (e.g., [61][62][63]). We observed that clonal species from the surrounding habitat dominated our newly-opened patches created by pepperweed elimination.…”
Section: Discussionmentioning
confidence: 99%